Preparation method of bio-based cellulose nano colorant

By combining cellulose nanocrystals with indigo dyes, high-pressure homogenization and ultrasonic treatment technology are used to prepare bio-based cellulose nanocolorants, which solves the problems of light color and poor stability of traditional nanocellulose colorants, and achieves high color depth and Stability avoids environmental pollution of dyes.

CN119286277APending Publication Date: 2025-01-10JIANGSU NEW REBA TECH CO LTD +1

Patent Information

Application Number
CN202411281779.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The traditional grafted nanocellulose colorant has a lighter color and poor stability, and the utilization rate of small-molecular dyes is not high, easy to migrate, and poor solvent resistance, which poses a risk of environmental pollution.

Method used

By hydrolysis of degreased cotton, a bio-based cellulose nanocrystal was prepared by combining cellulose nanocrystals with insoluble indigo dyes, and a bio-based cellulose nanocolorant was prepared by high-pressure homogenization and ultrasonic treatment technology to form a nano-level stable colorant.

Benefits of technology

It improves the color depth and stability of the colorant, overcomes the utilization rate and environmental pollution problems of traditional dyes, and provides better friction resistance and rheology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286277A_ABST
    Figure CN119286277A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a bio-based cellulose nano colorant, which comprises the following steps: (1) cutting absorbent cotton into pieces, and grinding to obtain cellulose powder; (2) mixing the cellulose powder with sulfuric acid, stirring and hydrolyzing under a water bath condition, then adding deionized water into a reaction solution, centrifuging, dispersing and dialyzing to prepare a pure fiber suspension; (3) performing high-pressure homogenization on the pure fiber suspension to obtain nano cellulose; and (4) preparing nanocellulose into a nanocellulose suspension, then adding the indigo dye dispersion liquid and a surfactant, carrying out ultrasonic treatment, and cooling to room temperature to prepare the bio-based cellulose nano colorant. The insoluble dye indigo blue is dispersed and then added into the nanocellulose to prepare the insoluble dye type nanocellulose coloring agent, so that the coloring agent has high color depth and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional nanofiber materials, and in particular to a method for preparing a bio-based cellulose nano colorant. Background Art

[0002] As the concept of green environmental protection has become more popular, energy conservation and emission reduction, green dyes have gradually become the focus of attention in the textile printing and dyeing industry. Traditional coloring technology mainly uses small molecule dyes and pigments, but small molecule dyes have problems such as low utilization rate, easy migration, poor solvent resistance, toxicity, and more complicated coloring process.

[0003] Polymer colorants have the color characteristics of small molecule dyes and the migration resistance, solvent resistance and processability of polymer materials, and are widely welcomed. Polymer colorants are a new type of colored polymer formed by introducing dye molecules into the main chain or side chain of polymers through certain chemical reactions. They are now widely used in textiles, leather, medicine, food processing, cosmetics and other industries.

[0004] Polymer colorants can be divided into two categories according to their skeleton types: synthetic polymer colorants and natural polymer colorants. The skeleton of synthetic polymer colorants is generally a polymer, such as polyether polymer colorants, polyamine polymer colorants and polyurethane polymer colorants. Natural polymer colorants are mostly based on natural polymer materials such as chitin, cellulose, protein, etc. As fossil resources such as coal, oil, and natural gas are consumed in large quantities, it is very meaningful to develop polymer colorants based on natural polymer compounds as the skeleton from the perspective of sustainable development.

[0005] Cellulose is renewable, biodegradable, and abundant, and has a long and complete technical foundation. Its derivatives have many important applications in the fiber, paper, polymer, and paint industries. Because reactive dyes are strong electrolytes, their addition to nanocellulose will greatly affect its stability. Therefore, the stability of traditional reactive dye-grafted nanocellulose inks is slightly poor. Summary of the invention

[0006] In order to overcome the problem that the grafted nanocellulose colorant has a lighter color and the soluble dye type nanocellulose colorant has a poor stability, the present invention provides a method for preparing a bio-based cellulose nano colorant. The present invention uses cotton as a raw material, obtains cellulose nanocrystals (CNC) by hydrolysis and separation, and combines them with insoluble dyes to prepare a bio-based cellulose nano colorant. It shows potential application prospects in the fields of coloring materials, water-based coatings, inks, etc.

[0007] The technical solution of the present invention is as follows:

[0008] The first object of the present invention is to provide a method for preparing a bio-based cellulose nano colorant, the preparation method comprising the following steps:

[0009] (1) Cutting and grinding the absorbent cotton to obtain cellulose powder;

[0010] (2) mixing the cellulose powder obtained in step (1) with sulfuric acid, stirring and hydrolyzing in a water bath, then adding deionized water to the reaction solution, centrifuging, dispersing, and dialyzing to obtain a pure fiber suspension;

[0011] (3) subjecting the purified fiber suspension obtained in step (2) to high pressure homogenization to obtain nanocellulose;

[0012] (4) The nanocellulose prepared in step (3) is formulated into a nanocellulose suspension, and then an indigo dye dispersion and a surfactant are added, ultrasonically treated, and cooled to room temperature to prepare a bio-based cellulose nanocolorant.

[0013] In one embodiment of the present invention, in step (2), the concentration of sulfuric acid is 62-66 wt %; and the ratio of cellulose powder to sulfuric acid is 1:5-10 g / mL.

[0014] In one embodiment of the present invention, in step (2), the stirring hydrolysis temperature is 40-60° C. and the time is 30-60 min.

[0015] In one embodiment of the present invention, in step (2), deionized water is added to the reaction solution to terminate the reaction, and then the supernatant is removed by centrifugation, the precipitate is stirred and dispersed in water again, and centrifuged again to remove the supernatant and take the precipitate product, that is, centrifugation is performed 2-3 times.

[0016] The precipitated product was dispersed in deionized water, the pH was adjusted to 7-8 with sodium hydroxide, and then dialyzed.

[0017] In one embodiment of the present invention, in step (2), dialysis is performed in deionized water for 1-2 weeks using a dialysis bag of 8000-14000 Daltons to remove excess salt components in the fiber slurry.

[0018] In one embodiment of the present invention, in step (2), cellulose powder is mixed with sulfuric acid and stirred for hydrolysis in a water bath, and the acid molecules diffuse into the cellulose microfibrils, causing the glycosidic bonds in the cellulose molecular chains along the amorphous domains of the cellulose fibrils to break, thereby causing the hierarchical structure of the fibril bundles to break to form CNCs;

[0019] Deionized water is added to the reaction solution to terminate the reaction process, and then centrifuged, the supernatant is poured out, the centrifuged precipitate is stirred and dispersed in deionized water again, and centrifuged again and the supernatant is removed; the precipitate is evenly dispersed in deionized water, and the residual acid in the precipitate dispersion is neutralized with NaOH (so that the final pH value is 7-8), and dialyzed in deionized water for 1-2 weeks with a dialysis bag of 8000-14000 Daltons to remove excess salt components in the fiber slurry to obtain a pure fiber suspension.

[0020] In one embodiment of the present invention, in step (3), the high pressure homogenization condition is 15000-25000 psi, and the number of homogenization cycles is 2-7 times.

[0021] The size of the prepared nanocellulose is: 30-100nm in diameter and 100-300nm in length.

[0022] The pure fiber suspension is homogenized into nanocellulose by a micro-jet high-pressure homogenizer; the material enters the homogenizer, flows through a one-way valve, is pressurized in a high-pressure chamber pump, and is squeezed and ejected from a micron-sized nozzle, impacting the emulsification chamber at a subsonic speed, while the fiber suspension is dispersed into nanometer size through strong cavitation and shear effects.

[0023] In one embodiment of the present invention, in step (4), the concentration of the nanocellulose suspension is 0.5-10 wt %.

[0024] In one embodiment of the present invention, in step (4), the concentration of the indigo dye dispersion is 0.5-20 g / L.

[0025] In one embodiment of the present invention, the preparation method of the indigo dye dispersion is: adding indigo dye to deionized water, followed by mechanical stirring, ultrasonic treatment for 10 minutes, cooling with ice water, and repeating the steps of mechanical stirring, ultrasonic treatment, and cooling until the indigo color depth no longer changes significantly after ultrasonication.

[0026] In one embodiment of the present invention, in step (4), the amount of indigo dye used is 1-5wt% of the nanocellulose suspension; the amount of surfactant used is 0.01-0.1wt% of the nanocellulose suspension.

[0027] In one embodiment of the present invention, in step (4), the surfactant is one of a polyether alcohol nonionic surfactant, an alkoxy polyethylene hydroxyethanol nonionic surfactant, and a polyethylene glycol nonionic surfactant.

[0028] In one embodiment of the present invention, in step (4), the conditions for ultrasonic treatment are: power is 500 W, each ultrasonic cycle is 5 seconds, wherein ultrasonication is performed for 2 seconds and then stabilized for 3 seconds, for a total of 10 minutes; and ultrasonication is repeated 3-5 times.

[0029] The second object of the present invention is to provide a printing paste containing the bio-based cellulose nano colorant prepared by the above preparation method.

[0030] The beneficial technical effects of the present invention are:

[0031] The invention disperses insoluble dye indigo and then adds it into nanocellulose to prepare insoluble dye type nanocellulose colorant, so as to make the colorant have high color depth and good stability.

[0032] The colorant of the present invention overcomes the problems of low utilization rate, easy migration, poor solvent resistance, exudation and toxicity of small molecule dyes. The cellulose colorant prepared by the present invention has a nanometer-level size, good stability and rheological properties, and solves the problems of poor stability of traditional colorants. Moreover, cellulose, as a natural degradable substance, solves the problems of biological toxicity and environmental pollution of traditional colorants. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the microstructure diagram of nanocellulose obtained in Example 1. DETAILED DESCRIPTION

[0034] The present invention will be described in detail below in conjunction with the embodiments.

[0035] The test method involved in the present invention is:

[0036] 1. Morphology: The morphology of cellulose nanocrystals was characterized by transmission electron microscopy (JEOL JEM-2100, Japan).

[0037] 2. Particle size: The particle size and distribution of the cellulose suspension were determined by a laser particle size analyzer (Microtrac S3500, USA).

[0038] 3. Printing fastness: The abrasion resistance of printed fabrics was measured by a rubbing color fastness tester (Y571D, China).

[0039] Embodiment 1:

[0040] A method for preparing a bio-based cellulose nano colorant, the preparation method comprising the following steps:

[0041] (1) Cutting and grinding the absorbent cotton to obtain cellulose powder;

[0042] (2) 1 g of the cellulose powder obtained in step (1) was mixed with 8 mL of sulfuric acid (with a concentration of 64 wt%), and the mixture was stirred and hydrolyzed in a water bath at 60° C. for 60 min. Deionized water was then added to the reaction solution to terminate the reaction process, and the mixture was centrifuged, the supernatant was discarded, the centrifuged precipitate was stirred and dispersed in deionized water again, and the mixture was centrifuged again and the supernatant was removed; the precipitate was uniformly dispersed in deionized water, the acid remaining in the precipitate dispersion was neutralized with NaOH (to make the pH value 7), and the mixture was dialyzed in deionized water with a dialysis bag of 8000-14000 Daltons for 1 week to remove excess salt components in the fiber slurry and obtain a pure fiber suspension;

[0043] (3) homogenizing the purified fiber suspension obtained in step (2) into nanocellulose using a microfluidizer; the high pressure homogenization condition is 20,000 psi, and the number of homogenization cycles is 5 times; the size of the obtained nanocellulose is: diameter 50-80 nm, length 130-200 nm;

[0044] (4) adding indigo dye to deionized water, followed by mechanical stirring, ultrasonic treatment for 10 min, cooling with ice water, and repeating the steps of mechanical stirring, ultrasonic treatment, and cooling until the color depth of indigo no longer changes significantly after ultrasonic treatment, to obtain an indigo dye dispersion with a concentration of 5 g / L;

[0045] The nanocellulose was dispersed in deionized water to prepare 500 g of nanocellulose suspension (concentration 2 wt%), and then 1.5 L of indigo dye dispersion and 0.25 g of polyether alcohol nonionic surfactant were added, and ultrasonic treatment was performed. The conditions of the ultrasonic treatment were: the power was 500 W, each ultrasonic cycle was 5 seconds, wherein the ultrasonic was continued for 2 seconds and then stabilized for 3 seconds, for a total of 10 minutes; the ultrasonic treatment was repeated 3 times, and the suspension was cooled to room temperature to obtain a bio-based cellulose nano colorant.

[0046] Figure 1 The microstructure of the obtained nanocellulose, (a) (b) is CNC powder. (c) (d) is CNC suspension. It can be concluded that the size of the cellulose nanocrystals prepared under the condition of 64wt% H2SO4 is 50-80nm in diameter and 130-200nm in length. The obtained cellulose nanocrystals are small in size and uniform in dispersion.

[0047] Embodiment 2:

[0048] A method for preparing a bio-based cellulose nano colorant, the preparation method comprising the following steps:

[0049] (1) Cutting and grinding the absorbent cotton to obtain cellulose powder;

[0050] (2) 1 g of the cellulose powder obtained in step (1) was mixed with 8 mL of sulfuric acid (with a concentration of 64 wt%), and the mixture was stirred and hydrolyzed in a water bath at 60° C. for 60 min. Deionized water was then added to the reaction solution to terminate the reaction process, and the mixture was centrifuged, the supernatant was discarded, the centrifuged precipitate was stirred and dispersed in deionized water again, and the mixture was centrifuged again and the supernatant was removed; the precipitate was uniformly dispersed in deionized water, the acid remaining in the precipitate dispersion was neutralized with NaOH (to make the pH value 7), and the mixture was dialyzed in deionized water with a dialysis bag of 8000-14000 Daltons for 1 week to remove excess salt components in the fiber slurry and obtain a pure fiber suspension;

[0051] (3) homogenizing the purified fiber suspension obtained in step (2) into nanocellulose using a microfluidizer; the high pressure homogenization condition is 20,000 psi, and the number of homogenization cycles is 5 times; the size of the obtained nanocellulose is: diameter 50-80 nm, length 130-200 nm;

[0052] (4) adding indigo dye to deionized water, followed by mechanical stirring, ultrasonic treatment for 10 min, cooling with ice water, and repeating the steps of mechanical stirring, ultrasonic treatment, and cooling until the color depth of indigo no longer changes significantly after ultrasonic treatment, to obtain an indigo dye dispersion with a concentration of 5 g / L;

[0053] The nanocellulose was dispersed in deionized water to prepare 500 g of nanocellulose suspension (concentration 5 wt%), and then 1.5 L of indigo dye dispersion and 0.25 g of polyether alcohol nonionic surfactant were added, and ultrasonic treatment was performed. The conditions of the ultrasonic treatment were: the power was 500 W, each ultrasonic cycle was 5 seconds, wherein the ultrasonic was maintained for 2 seconds and then stabilized for 3 seconds, for a total of 10 minutes; the ultrasonic treatment was repeated 3 times, and the suspension was cooled to room temperature to obtain a bio-based cellulose nano colorant.

[0054] Embodiment 3:

[0055] A method for preparing a bio-based cellulose nano colorant, the preparation method comprising the following steps:

[0056] (1) Cutting and grinding the absorbent cotton to obtain cellulose powder;

[0057] (2) 1 g of the cellulose powder obtained in step (1) was mixed with 8 mL of sulfuric acid (with a concentration of 64 wt%), and the mixture was stirred and hydrolyzed in a water bath at 60° C. for 60 min. Deionized water was then added to the reaction solution to terminate the reaction process, and the mixture was centrifuged, the supernatant was discarded, the centrifuged precipitate was stirred and dispersed in deionized water again, and the mixture was centrifuged again and the supernatant was removed; the precipitate was uniformly dispersed in deionized water, the acid remaining in the precipitate dispersion was neutralized with NaOH (to make the pH value 7), and the mixture was dialyzed in deionized water with a dialysis bag of 8000-14000 Daltons for 1 week to remove excess salt components in the fiber slurry and obtain a pure fiber suspension;

[0058] (3) homogenizing the purified fiber suspension obtained in step (2) into nanocellulose using a microfluidizer; the high pressure homogenization condition is 20,000 psi, and the number of homogenization cycles is 5 times; the size of the obtained nanocellulose is: diameter 50-80 nm, length 130-200 nm;

[0059] (4) adding indigo dye to deionized water, followed by mechanical stirring, ultrasonic treatment for 10 min, cooling with ice water, and repeating the steps of mechanical stirring, ultrasonic treatment, and cooling until the color depth of indigo no longer changes significantly after ultrasonic treatment, to obtain an indigo dye dispersion with a concentration of 5 g / L;

[0060] The nanocellulose was dispersed in deionized water to prepare 500 g of nanocellulose suspension (concentration 7 wt%), and then 1.5 L of indigo dye dispersion and 0.25 g of polyether alcohol nonionic surfactant were added, and ultrasonic treatment was performed. The conditions of the ultrasonic treatment were: the power was 500 W, each ultrasonic cycle was 5 seconds, wherein the ultrasonic was maintained for 2 seconds and then stabilized for 3 seconds, for a total of 10 minutes; the ultrasonic treatment was repeated 3 times, and the suspension was cooled to room temperature to obtain a bio-based cellulose nano colorant.

[0061] Embodiment 4:

[0062] A method for preparing a bio-based cellulose nano colorant, the preparation method comprising the following steps:

[0063] (1) Cutting and grinding the absorbent cotton to obtain cellulose powder;

[0064] (2) 1 g of the cellulose powder obtained in step (1) was mixed with 8 mL of sulfuric acid (with a concentration of 64 wt%), and the mixture was stirred and hydrolyzed in a water bath at 60° C. for 60 min. Deionized water was then added to the reaction solution to terminate the reaction process, and the mixture was centrifuged, the supernatant was discarded, the centrifuged precipitate was stirred and dispersed in deionized water again, and the mixture was centrifuged again and the supernatant was removed; the precipitate was uniformly dispersed in deionized water, the acid remaining in the precipitate dispersion was neutralized with NaOH (to make the pH value 7), and the mixture was dialyzed in deionized water with a dialysis bag of 8000-14000 Daltons for 1 week to remove excess salt components in the fiber slurry and obtain a pure fiber suspension;

[0065] (3) homogenizing the purified fiber suspension obtained in step (2) into nanocellulose using a microfluidizer; the high pressure homogenization condition is 20,000 psi, and the number of homogenization cycles is 5 times; the size of the obtained nanocellulose is: diameter 50-80 nm, length 130-200 nm;

[0066] (4) adding indigo dye to deionized water, followed by mechanical stirring, ultrasonic treatment for 10 min, cooling with ice water, and repeating the steps of mechanical stirring, ultrasonic treatment, and cooling until the color depth of indigo no longer changes significantly after ultrasonic treatment, to obtain an indigo dye dispersion with a concentration of 5 g / L;

[0067] The nanocellulose was dispersed in deionized water to prepare 500 g of nanocellulose suspension (concentration 7%), and then 3 L of indigo dye dispersion and 0.25 g of polyether alcohol nonionic surfactant were added, and ultrasonic treatment was performed. The conditions of the ultrasonic treatment were: the power was 500 W, each ultrasonic cycle was 5 seconds, wherein the ultrasonic was maintained for 2 seconds and then stabilized for 3 seconds, for a total of 10 minutes; the ultrasonic treatment was repeated 3 times and the suspension was cooled to room temperature to obtain a bio-based cellulose nano colorant.

[0068] Comparative Example 1:

[0069] Same as Example 3, except that 56 wt% H2SO4 was used to hydrolyze the cellulose fiber powder.

[0070] Comparative Example 2:

[0071] Same as Example 3, except that 60 wt% H2SO4 was used to hydrolyze the cellulose fiber powder.

[0072] Comparative Example 3:

[0073] Same as Example 3, except that 68 wt% H2SO4 was used to hydrolyze the cellulose fiber powder.

[0074] Results

[0075] The cellulose nanoparticles prepared in Example 3 and the cellulose nanoparticles prepared in Comparative Examples 1-3 were subjected to relevant performance tests, and the results are shown in Table 1 below.

[0076] Table 1

[0077]

[0078] It can be seen from Table 1 that when the sulfuric acid concentration is 64%, the hydrolysis yield is the highest and the nanocellulose size remains at a relatively small value. When the sulfuric acid concentration is 56% and 60%, the hydrolysis yield is less than 45% and the size is larger. When the sulfuric acid concentration is 68%, the size is the smallest, but the hydrolysis yield is the lowest at 20%.

[0079] The cellulose nano colorants prepared in Examples 1-4 and Comparative Examples 1-3 were applied to screen printing of textiles; the printing paste was prepared by stirring 100 mL of the prepared cellulose nano colorant suspension (2.5 wt%) with 0.10 g of sodium carboxymethyl cellulose (CMC) for 0.5 h, then adding 0.15 g of 1,2,3,4-butanetetracarboxylic acid (BTCA) and 0.05 g of sodium hypophosphite (SHP) to obtain a printing paste.

[0080] The base fabric used for printing is cotton fabric. The target color paste is printed on the cotton fabric with a screen printing plate, and then the printed fabric is baked at 165°C for 3 min. 300 mL of soap boiling solution containing 1 mol / L detergent and 1 mol / L Na2CO3 is prepared. The baked printed fabric is soap boiled at 80°C for 10 min, then washed with water, and dried at 70°C for 30 min to obtain the printed fabric.

[0081] When the dry friction fastness of the fabric was tested using a friction fastness tester, there was no obvious staining on the lining cloth, and the colorimetric gray card showed a grade of five; when the fabric was tested for wet friction fastness, the colorimetric gray card showed a grade of four.

[0082] Table 2

[0083] sample Dry rubbing fastness Wet rubbing fastness Example 1 Level 5 Level 4 Example 2 Level 5 Level 4 Example 3 Level 5 Level 4 Example 4 Level 5 Level 4 Comparative Example 1 Level 4 Level 3 Comparative Example 2 Level 4 Level 3 Comparative Example 3 Level 4 Level 3

[0084] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for preparing a bio-based cellulose nano colorant, characterized in that: The preparation method comprises the following steps: (1) Cut and grind the absorbent cotton to obtain cellulose powder; (2) mixing the cellulose powder obtained in step (1) with sulfuric acid, stirring and hydrolyzing in a water bath, then adding deionized water to the reaction solution, centrifuging, dispersing, and dialyzing to obtain a pure fiber suspension; (3) subjecting the purified fiber suspension obtained in step (2) to high pressure homogenization to obtain nanocellulose; (4) The nanocellulose prepared in step (3) is formulated into a nanocellulose suspension, and then an indigo dye dispersion and a surfactant are added, ultrasonically treated, and cooled to room temperature to prepare a bio-based cellulose nanocolorant.

2. The preparation method according to claim 1, characterized in that: In step (2), the concentration of sulfuric acid is 62-66 wt %; the ratio of cellulose powder to sulfuric acid is 1:5-10 g / mL.

3. The preparation method according to claim 1, characterized in that: In step (2), the stirring hydrolysis temperature is 40-60° C. and the time is 30-60 min.

4. The preparation method according to claim 1, characterized in that: In step (2), the dialysis is performed using a dialysis bag of 8000-14000 Daltons in deionized water for 1-2 weeks.

5. The preparation method according to claim 1, characterized in that: In step (3), the high pressure homogenization condition is 15000-25000 psi, and the number of homogenization cycles is 2-7 times; the size of the obtained nanocellulose is: diameter 30-100 nm, length 100-300 nm.

6. The preparation method according to claim 1, characterized in that: In step (4), the concentration of the nanocellulose suspension is 0.5-10 wt %.

7. The preparation method according to claim 1, characterized in that: In step (4), the concentration of the indigo dye dispersion is 0.5-20 g / L.

8. The preparation method according to claim 1, characterized in that: In step (4), the amount of indigo dye used is 1-5wt% of the nanocellulose suspension; the amount of surfactant used is 0.01-0.1wt% of the nanocellulose suspension.

9. The preparation method according to claim 1, characterized in that: In step (4), the ultrasonic treatment conditions are: power of 500 W, each ultrasonic cycle of 5 seconds, wherein ultrasonication for 2 seconds is followed by stabilization for 3 seconds, for a total of 10 minutes; and ultrasonication is repeated 3-5 times.

10. A printing paste, characterized in that: A bio-based cellulose nano colorant prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Water-free color regenerated cellulose color paste printing process

    CN109235084A

  • High-stability nano-cellulose based neutral ink and preparation method thereof

    CN110041756A

  • Preparation method of degradable hydrophobic coating

    CN114702888A

  • Cationic dyes and uses thereof

    CN118574858A

  • Textile dyeing using nanocellulosic fibers

    US20160010275A1

Cited By

  • Nitrocellulose-based macromolecular coloring agent as well as preparation method and application thereof

    CN120904362A

  • Hydroxyethyl cellulose ether-based polymeric dye as well as preparation method and application thereof

    CN121160114A